Obstructive sleep apnea, detected by the Berlin Questionnaire: an associated risk factor for coronary artery disease Risco de apneia obstrutiva do sono detectado pelo Questionário de Berlim está associado com doença arterial coronariana - Daniela Massierer; Denis Martinez; Sandra Costa Fuchs; Paulo P. Pellin; Márcio S. Garcia; Ana Luisa Zacharias; Isadora F. Antunes; Marco V. Wainstein; Leila Beltrami Moreira; Jorge Pinto Ribeiro; Flavio Danni Fuchs (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Obstructive sleep apnea (OSA), a risk factor for coronary artery disease, remains under diagnosed. We investigated if OSA identified by the Berlin Questionnaire (BQ) is associated with the risk of coronary artery disease. Cases were patients referred for elective coronariography. The cases were classified with significant coronary lesions (stenosis > 50% in an epicardial coronary) or without significant coronary lesions. Controls were selected from a population-based sample. Positive BQ results were identified in 135 (41.2%) of 328 cases, in contrast with 151 (34.4%) of 439 control subjects (p = 0.03). In a multinomial logistic analysis, the risk for OSA identified by the BQ was independently associated with coronary artery disease in cases with lesions of at least 50% (OR = 1.53; 95%CI: 1.02-2.30; p = 0.04). The risk from OSA identified by the BQ was higher in younger subjects (40-59 years) (OR = 1.76; 95%CI: 1.05-2.97; p = 0.03) and in women (OR = 3.56; 95%CI: 1.64-7.72; p = 0.001). In conclusion, OSA identified by the BQ greatly increases the risks of coronary artery disease in patients having significant coronary artery lesions indicated by anangiogram, particularly in younger individuals and in women. Síndrome da apneia obstrutiva do sono (SAOS), fator de risco para doença arterial coronariana, permanece subdiagnosticada. Investigou-se se o risco de SAOS pelo Questionário de Berlim (QB) associa-se com doença arterial coronariana. Casos foram pacientes encaminhados para coronariografia eletiva, classificados em casos com lesão significativa (estenose > 50%) ou sem lesões significativas. Controles foram selecionados em amostra populacional. QB foi positivo em 135 (41,2%) de 328 casos, em contraste com 151 (34,4%) de 439 controles (p = 0,03). Em análise logística multinomial, o risco de SAOS identificado pelo QB associou-se com doença arterial coronariana exclusivamente nos casos com lesões de pelo menos 50% (OR: 1,53; IC95%: 1,02-2,30; p = 0,04). Em indivíduos com lesões significativas, o risco de SAOS pela QB foi maior entre os que têm 40-59 anos (OR: 1,76; IC95%: 1,05-2,97; p = 0,03) e em mulheres (OR: 3,56; IC95%: 1,64-7,72; p = 0,001). Em conclusão, alto risco para a SAOS identificados pela QB associa-se a risco de lesões coronarianas significativas na angiografia, particularmente em indivíduos mais jovens e em mulheres.